PENINGKATAN MOTIVASI BELAJAR MELALUI METODE PEMBERIAN TUGAS TERSTRUKTUR PADA MATA PELAJARAN MENGOLAH MAKANAN INDONESIA - Maidesti, Vitria; Elida, Elida; Syarif, Wirnelis (Journal of Home Economics and Tourism, 2013)
This research aims to increase students’ motivation by using a structured task giving the subjects Indonesian Food processing in SMK N 3 Solok City. It is characterized by frequent permission during school hours, sleepy, dreamy, noisy during lessons, toggle seat while studying, and lack of student initiative in learning. This type of research is a classroom action research. Subject were students of SMK N 3 Solok City Program Study Membership Arrange Boga class XI 2012-2013 school year with amount of student 20 people. Techniques of data collection using questionnaires and observation sheets. The results showed that the method could improve the provision of structured task motivation that ultimately improve student learning outcomes. For that, use a variety of method need to be applied to the teacher in the learning process. One of which is a method of providing structured task. Keywords: motivation to learn, structured task, Indonesian food processing